THE EFFECT OF REGIONAL SPILLOVERS ON ECONOMIC GROWTH IN PEKANBARU CITY, RIAU PROVINCE, INDONESIA - M. Irfan; Sinta Yulyanti (International Journal of Economics Development Research (IJEDR), 2020)
The economic activities of one region can provide abundant economic growth for other areas. This research discusses the reciprocal relationship between economic growth in Pekanbaru City and economic growth in Siak Regency, Pelalawan Regency, and Kampar Regency. Using quantitative methods and secondary data from the Central Bureau of Statistics was analyzed using the Two-Stage Least Square method then regressed using the Eviews 10 application. The results showed a positive and significant reciprocal relationship at ? 0.05 between Pekanbaru city GRDP and Siak Regency GRDP. Coefficients 0.9626 and 1.0890. The expected effect of GRDP of Pekanbaru City and GRDP of Pelalawan Regency with a coefficient of 3.4663 and 0.2864 at ? 0.05. Whereas Kampar Regency only has a unidirectional relationship, namely, the GRDP of Pekanbaru City has a positive and significant effect on Kampar's GRDP with a coefficient of 0.9527 at ? 0.10. Apart from being caused by geographic conditions, this reciprocal influence is caused by leading sectors, including the pulp and paper processing industry, the oil and gas mining sector, and the oil palm plantation sector, which delegate economic activities between Siak Regency and Pelalawan Regency with Pekanbaru City. Meanwhile, GRDP Pekanbaru City and GRDP Kampar Regency only provide unidirectional spillover due to the dominance of the trade and construction sector in Pekanbaru City.